Determinants of Satisfaction With Hospital Online Appointment Service Among Older Adults During the COVID-19 Pandemic: A Cross-Sectional Study - Li, Wenjia; Shen, Shengwei; Yang, Jidong; Guo, Jingyu; Tang, Qinghe (Frontiers in Public Health, 2022)
Background: How did the elderly who had to use online medical service during the COVID-19 pandemic bridge the "digital divide"? Taking Internet-based appointment service (IBAS) as an example, this study aimed to investigate the subjective feelings of the elderly and evaluate their user-satisfaction. Methods: This study was based on data from a questionnaire survey involving 325 outpatients 60 years old in shanghai during the COVID-19 pandemic. The satisfaction of IBAS was evaluated and compared from six domains including convenience, visiting time, correct identification of specialists, on-site assist service, COVID-19 prevention, and privacy protection. Logistic regression analysis was used to investigate the correlation between satisfaction and social factors. Results: No significant difference between the elderly with or without previous experience using IBAS in terms of overall satisfaction. In the domain of operation difficulty (81.9% vs 97.5%) and precise medicine (88.1% vs 96.9%), such as correctly identifying the specialist, the satisfaction of previous user group was significantly higher than that of first-time user group. However, there was no significant difference in the remaining four domains between the two groups. Among the first time IBAS users, the satisfaction was higher than the walk-in registration they used before. Logistic regression revealed that some “intention to use IBAS”-associated social factors such as distance from the hospital, living status, and frequency of hospital visit, were related to the satisfaction of the elderly. Conclusions: Driven by the external pandemic and internal intention, the elderly would choose and manage network medical resources with their high satisfaction, which essentially demonstrates not only behavioral adjustment but also inner acceptance in older adults. Our findings support the need for promoting the driving force of the elderly in using Internet-based medical service as well as transforming their behavior patterns and habit formation.